Crossing a Canal and pay the price or go the distance and we all pay the price - Zis, Thalis (My University, 2021)
The pandemic outbreak of Covid-19 led to a sharp decline in demand for oil and historically low fuel prices. Where we go from here is unclear while the pandemic is still affecting the global economy, but it can be anticipated that in the short-term oil production will be reduced. From a ship operator’s perspective, the very low fuel prices may lead to increased sailing speeds for certain sectors (particularly liner shipping), while product and crude tankers may wait things out until fuel prices increase again. A very interesting development is that certain ship operators sail around Africa instead of passing (and paying fees) through the Suez Canal, due to the low fuel prices that make this profitable. In response, the Suez Canal authorities offered rebates up to 17% for containerships from May through to June 2020. The objective of this paper is to examine how canal authorities decided to provide financial incentives to ship operators for choosing to cross their canals, and assess the economic and environmental impacts of this choice. The methodology considers the use of an activity-based model to estimate fuel consumption, and calculate costs and emissions from the different options available to the ship operator. The perspectives of all stakeholders (ship operator, ship owner, canal authorities, and the society) are examined. The importance of market-based measures and the external costs of emissions are discussed, with a forward-looking view for the implementation of the Initial IMO strategy for the decarbonisation of maritime shipping
Keywords: Canal authorities; Financial incentives